SOSIALISASI PERANCANGAN PLC MENGGUNAKAN RASPBERRY PICO UNTUK PEMBELAJARAN SISWA SMK - Suryo, Yoedo Ageng (Intimas, 2025)
This community service program was implemented to introduce alternative learning of programming using Programmable Logic Controller. The problem of vocational high school students is the ability to have hardware independently and continuous learning outside of school hours. This activity includes socialization, theory and direct practice on how to make Raspberry Pico into Mitsubishi FX1N PLC. The methods used include socialization, theory and direct practice starting from configuring Raspberry Pico microcontroller into PLC to programming. Successness is shown by the students' interest and willingness to learn independently. The target level of community service activities is quite implemented with the enthusiasm of the participants and the adjustment of the success of the methods used. This activity has a positive impact in the form of increased understanding of the material, the ability to modify problems and solutions according to students' creativity. The follow-up to this activity is in the form of ongoing cooperation between vocational high schools and campuses to deepen students' logical abilities in dealing with production process problems in the industrial world.